MAGMA : Museum of Avant-Garde Mastery. - Glotser, Vatslav; Kantor, Viatcheslav; Tolstoy, Andrey; Epshteyn, Mikhail (Moscow : MAGMA: Museum of Avant-Garde Mastery, 2015)
Repin, Ilya ; Serov, Valentin ; Bakst, Léon ; Altman, Nathan ; Shterenberg, David ; Pevsner, Antoine ; Modigliani, Amedeo ; Serebriakova, Zinaida ; Falk, Robert ; Chagall, Marc ; Zadkine, Ossip ; Gabo, Naum ; Lissitzky, El ; Lipchitz, Jacques ; Soutine, Chaïm ; Delaunay, Sonia ; Gudiashvili, Lado ; Tyshler, Alexander ; Nevelson, Louise ; Rothko, Mark ; Freud, Lucian ; Weisberg, Vladimir ; Lion, Dmitry ; Shvartsman, Mikhail ; Bulatov, Erik ; Kabakov, Ilya ; Yakovlev, Vladimir ; Pivovarov, Viktor ; Steinberg, Eduard ; Yankilevsky, Vladimir ; Kuper, Yuri ; Bruskin, Grisha
boek